Multiple pilomatricomas with somatic CTNNB1 mutations in children with constitutive mismatch repair deficiency. Issue 7 (30th April 2013) - Chmara, Magdalena; Wernstedt, Annekatrin; Wasag, Bartosz; Peeters, Hilde; Renard, Marleen; Beert, Eline; Brems, Hilde; Giner, Tina; Bieber, Imke; Hamm, Henning; Sciot, Raf; Wimmer, Katharina; et al.
<x xml:space="preserve">Abstract</x> Constitutional mismatch repair deficiency (CMMR‐D) due to biallelic germline mutations in one of four mismatch repair genes causes a childhood cancer syndrome characterized by a broad tumor spectrum including hematological malignancies, and brain and Lynch syndrome‐associated tumors. Herein, we report three children who had in addition to CMMR‐D‐associated malignancies multiple pilomatricomas. These are benign skin tumors of hair matrical differentiation frequently associated with somatic activating mutations in the ß‐catenin gene CTNNB1. In two of the children, the diagnosis of CMMR‐D was confirmed by the identification of biallelic germline PMS2 mutations. In the third individual, we only found a heterozygous germline PMS2 mutation. In all nine pilomatricomas with basophilic cells, we detected CTNNB1 mutations. Our findings indicate that CTNNB1 is a target for mutations when mismatch repair is impaired due to biallelic PMS2 mutations. An elevated number of activating CTNNB1 alterations in hair matrix cells may explain the development of multiple pilomatricomas in CMMR‐D patients. Of note, two of the children presented with multiple pilomatricomas and other nonmalignant features of CMMR‐D before they developed malignancies. To offer surveillance programs to CMMR‐D patients, it may be justified to suspect CMMR‐D syndrome in individuals fulfilling multiple nonmalignant features of CMMR‐D (including multiple pilomatricomas) and offer molecular testing in combination with interdisciplinary counseling. © 2013 Wiley Periodicals, Inc.